Influence of Rotation on Transversely Isotropic Piezoelectric Rod Coated with a Thin Film - Rajendran SELVAMANI; Oluwole Daniel MAKINDE (Engineering Transactions, 2018)
In this paper, the influence of rotation on axisymmetric waves of a piezoelectric rod coated with a thin film is studied using constitutive form linear theory elasticity and piezo-electric equations. Potential functions are introduced to uncouple the equations of motion in radial and axial directions. The surface area of the rod is coated by a perfectly conducting material. The frequency equations are obtained for longitudinal and flexural modes of vibration and are studied numerically for PZT-4 ceramics. The computed non-dimensional frequency, phase velocity, relative frequency shift, electromechanical coupling and electric displacement are presented in the form of dispersion curves. This type of study is important in the construction of rotating sensors and gyroscope.